2022
DOI: 10.2196/34973
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Embrace Artificial Intelligence Among Medical Doctors and Students: Questionnaire-Based Study

Abstract: Background Similar to understanding how blood pressure is measured by a sphygmomanometer, physicians will soon have to understand how an artificial intelligence–based application has come to the conclusion that a patient has hypertension, diabetes, or cancer. Although there are an increasing number of use cases where artificial intelligence is or can be applied to improve medical outcomes, the extent to which medical doctors and students are ready to work and leverage this paradigm is unclear. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…In this section, we estimate the usefulness of our preferred strategy in contrast to the previously mentioned methods for Chinese students' data for the given data. Our proposed technique method also matched with other standard techniques artificial intelligence (AI) [26], machine learning (ML) [27], particle swarm optimization-support vector machine (PSO-SVM) [28], and Fuzzy k nearest neighbor (F-KNN) [29]. Several significant disadvantages of artificial intelligence applications, according to AI, are the safety risk associated with submitting critical material to virtualized systems that may require proper security controls [30].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this section, we estimate the usefulness of our preferred strategy in contrast to the previously mentioned methods for Chinese students' data for the given data. Our proposed technique method also matched with other standard techniques artificial intelligence (AI) [26], machine learning (ML) [27], particle swarm optimization-support vector machine (PSO-SVM) [28], and Fuzzy k nearest neighbor (F-KNN) [29]. Several significant disadvantages of artificial intelligence applications, according to AI, are the safety risk associated with submitting critical material to virtualized systems that may require proper security controls [30].…”
Section: Discussionmentioning
confidence: 73%
“…The proposed method has enhanced accuracy due to the results obtained thus far. Existing works in AI [26], ML [27], PSO-SVM [28], and F-KNN [29] are compared using measures such as precision, F1 score, student performance, and accuracy. As a result, compared to existing works, the proposed CNN-AM performs better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Effective implementation strategies, however, are poorly developed, [10] and the potential for AI to replace (as opposed to support) clinical decision-making [11] currently outstrips the trust of many patients and professionals. [12,13] Whilst we are mindful of this wider perspective, in this clinical review we focus on selected examples to provide an expert perspective on the potential of telemedicine to deliver virtual respiratory care. We will consider how the COVID-19 pandemic has had a major influence on this story, promoting implementation of remote ways to monitor the progress of COVID in people at risk, [14][15][16][17][18] highlighting the potential of safely maintaining the care of people with non-communicable respiratory diseases, [19,20] and of supporting self-management during times of lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that many of these studies were specifically interested in AI use for radiology [26], particularly in Saudi Arabia [37][38][39]. In one multi-continent study, medical doctors and students had low levels of familiarity with AI, and only 2.9-9.8% had attended courses about AI [40]. Results of Saudi Arabian studies among medical doctors and students showed low levels of knowledge about AI despite the desire to learn.…”
Section: Introductionmentioning
confidence: 99%